Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.7326/m20-3213
|View full text |Cite
|
Sign up to set email alerts
|

Masks for Prevention of Respiratory Virus Infections, Including SARS-CoV-2, in Health Care and Community Settings

Abstract: Background: Recommendations on masks for preventing coronavirus disease 2019 (COVID-19) vary. Purpose: To examine the effectiveness of N95, surgical, and cloth masks in community and health care settings for preventing respiratory virus infections, and effects of reuse or extended use of N95 masks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
127
2
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(140 citation statements)
references
References 49 publications
1
127
2
5
Order By: Relevance
“…In the absence of clinical trials on SARS-CoV-2, trials on other viruses with similar infection patterns (i.e., documented droplet and suspected airborne transmission) are the best available alternatives. Recent systematic and narrative reviews comparing the effectiveness of respirators versus masks against common viral respiratory infections (including coronaviruses and influenza viruses such as H1N1) come to similar conclusions: both devices offer comparable protection in health care settings (23)(24)(25)(26)(27)(28)(29)(30)(31).…”
Section: Trials Comparing Masks and Respirators In Health Care Settingsmentioning
confidence: 90%
“…In the absence of clinical trials on SARS-CoV-2, trials on other viruses with similar infection patterns (i.e., documented droplet and suspected airborne transmission) are the best available alternatives. Recent systematic and narrative reviews comparing the effectiveness of respirators versus masks against common viral respiratory infections (including coronaviruses and influenza viruses such as H1N1) come to similar conclusions: both devices offer comparable protection in health care settings (23)(24)(25)(26)(27)(28)(29)(30)(31).…”
Section: Trials Comparing Masks and Respirators In Health Care Settingsmentioning
confidence: 90%
“…The Scientific Medical Policy Committee (SMPC), in collaboration with staff from ACP's Department of Clinical Policy, developed these practice points on the basis of a rapid systematic evidence review conducted by the Pacific Northwest Evidence-based Practice Center and funded by the Agency for Healthcare Research and Quality (1,2). The SMPC comprises 11 internal medicine physicians representing various clinical areas of expertise and 1 public (nonclinician) member, and includes members with expertise in epidemiology, healthy policy, and evidence synthesis.…”
Section: Appendix: Practice Points Development Processmentioning
confidence: 99%
“…The American College of Physicians (ACP) based these practice points on a rapid, living systematic evidence review funded by the Agency for Healthcare Research and Quality (1,2). See the Appendix (available at Annals.org) for methods used to develop the practice points.…”
Section: Introductionmentioning
confidence: 99%
“…10 The extent of risk modification with PPE remains unclear. [7][8][9]11 A recent prospective study in the UK and USA suggested a fivefold increased risk for HCW caring for patients with COVID-19 compared to HCW not caring for patients with COVID-19, even with the use of PPE, 12 while another study of HCW in a large healthcare system showed a decrease in positive tests for SARS-CoV-2 associated with a universal masking recommendation. 13 This heterogeneous landscape makes it difficult for the HCW community to determine actual risk of acquiring COVID-19 in healthcare vs. community settings and the effectiveness of various risk-mitigating strategies.…”
Section: Introductionmentioning
confidence: 99%